Romantic Philosophy in The Poem of The “Hadith al-Maqbarah” by Abū al-Qāsim al-Shābī | الفلسفية الرومانسية في قصيدة حديث المقبرة للشاعر أبي القاسم الشابي - Ahmadi Usman; Nelly Ayu (Fakultas Dirasat Islamiyah, Univitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2020)
The purpose of this research is to study and analyze the poem of Abu al-Qasim al-Shabi, which is characterized by romantic philosophical thoughts of death. Shabi lived in a short time due to heart disease. This disease is the main factor of his suffering and it influenced his poetry containing the story of his wounded heart, which is threatened by death every moment.This study uses the descriptive method in defining the personality of Abu al-Qasim al-Shabi and his contribution to the field of literature. Also, The analytical method is used to study and interpret the poem and its romantic philosophy. On the other hand, the author applies a literature study in conducting writing by collecting sources, references, journals, and academic research relating to this study.Among the results of this research: Al-Shabi’s poetry is distinguished by romantic philosophical ideas. moreover, this article divided this poem into seven parts. In each of these verses, al-Shabi's questions about immortality and annihilation revealed. These questions indicate the philosophical poetry of al-Shabi as he thinks to find the answers for questions raised. Further, al-Shabi showed this philosophy in romantic expression with rhetorical elements.